Adjusted linear quadratic regulator-proportional-derivative control of Quanser’s three degrees of freedom helicopter based on flower pollination algorithm under external disturbances - Ghiloubi, Imam Barket; Abdou, Latifa; Lahmar, Oussama (IAES International Journal of Robotics and Automation (IJRA), 2024)
External disturbances, saturation of actuator motors, and limits of certain angular movements are commonly encountered in robotic systems, particularly those involving flight, and they present the most common and influential factors affecting the stability and performance of these systems. In this paper, a hybrid controller for a three-degree-of-freedom (3-DoF) helicopter is designed and applied to this flying robot system, taking into account the previously mentioned constraints. The proposed hybrid controller integrates proportional-derivative (PD) control with an adjusted linear quadratic regulator (ALQR) using the flower pollination algorithm (FPA) optimization method. Simulation results of travel (λ), elevation (ε), and pitch (ρ) responses, as well as experimental results of elevation and travel tracking responses under external disturbances using the bench-top Quanser’s (3-DoF) helicopter, demonstrate the robustness and good performance of the controlled system using the proposed method. The effectiveness of the proposed method is compared to several methods in the literature.